Engaging Communities in the 'Big Society': What Impact is the Localism Agenda having on Community Archaeology?. (March 2014) - Jackson, Stella; Lennox, Rob; Neal, Cath; Roskams, Steve; Hearle, John; Brown, Louise
<x content-type="archive" xml:space="preserve">Abstract</x> When the UK Coalition Government came to power in May 2010, its members brought with them a localism agenda, based upon what they called the 'Big Society'. This agenda was focused on community engagement and devolvement of power, and has seen a number of legislative and policy changes in the UK, with the 2012 Localism Act devolving powers to local government, and providing means for local communities to become involved in decision making, inspire volunteerism, and support social enterprise. This paper draws upon debates which have arisen within the archaeological sector relating to the broad influence of the localism agenda on its work, with individual contributors taking various positions regarding theoretical analysis of the Big Society in relation to the social goals of archaeology. The contributors ask, respectively: what is it that we do which can be thought of as the Big Society, and what is its meaning against the context of the socially focused archaeology work already done by the sector? What limitations must we be aware of, and how can we make the most of the opportunities? Critical consideration is then given to why archaeologists should be interested in political agendas such as this.